Child Hand Washing Intervention (Age < 5 Years) Against The Risk of Infection in Child Care: Systematic Review - Winda Agus Tina; Joni Haryanto; Retno Indarwati (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The risk of infection experienced by children (age < 5 years) who do not wash their hands properly becomes a serious threat to the health. Purpose: The study aims to explain handwashing interventions in child care facilities against the risk of infection. A systematic review was obtained from Scopus, PubMed, Science Direct, SAGE and ProQuest database, published between 2010-2020. The study design; Narrative analysis of the study's findings has been conducted. A total of 25 studies covered about comprehensive handwashing interventions (n=18) and behavior (n=7). The average number of participants more than one hundred respondents. Dealing with hand washing is essential in first aid to prevent the risk of infection in children aged < 5 years. Various interventions can have a significant effect on reducing the risk of infection although other interventions provide different successes.